MENINGKATKAN ENGLISH AWARENESS DENGAN FUN LISTENING ACTIVITY - Dwi Meisyitah Ananda (Jurnal Pengabdian Masyarakat Kesosi, 2023)
Language awareness is a term that can help students use and learn English better. Language awareness that is owned will help motivate when someone learns a language. However, English as EFL (English as Foreign Language) in Indonesia presents a challenge to students who have minimal exposure to English. This community service aims to promote language awareness by using activities such as the interactive Fun Listening Activity. Respondents in this activity were parents of school students. The evaluation of this activity was considered good and enthusiastic parents could get ideas for a fun way of learning English for their children. After the community service activities were completed in the form of counseling, it can be concluded that respondents who took part in the activities were able to get new and fun ideas while learning English.